Prevention of preeclampsia with acetylsalicylic acid: a brief history of use and modern prevention methods - R.S. Osipov; L.S. Dzhokhadze; P.A. Kuznetsov; V.V. Shamugiya (РМЖ. Мать и дитя, 2023)
R.S. Osipov1, L.S. Dzhokhadze2, P.A. Kuznetsov2, V.V. Shamugiya3 1Moscow Regional Research Institute of Obstetrics and Gynecology, Moscow, Russian Federation 2Pirogov Russian National Research Medical University, Moscow, Russian Federation 3Branch of the V.V. Veresaev City Clinical Hospital, Moscow, Russian Federation By preeclampsia (PE) we mean hypertension, which first occurred after 20 weeks pregnant in combination with proteinuria or other signs of target organ damage. PE is accompanied by high maternal and perinatal mortality, and these indicators are the higher the earlier the disease onset is. Despite the presence of seemingly effective methods for the PE prevention, this pathology incidence has practically not changed in recent decades. This may be due to the fact that the PE pathogenesis is complex and has not been fully studied. We are still continuing to look for new prognostic markers that would allow us to select high-risk patients. In the high-risk group, acetylsalicylic acid (ASA) intake reduces the PE incidence, but the overall picture does not change significantly. Besides, ASA long-term use may increase the risks of some pregnancy complications. Differential treatment tactics for prevention in different risk groups is likely to be effective. The article summarizes the confirmed data on ASA used for the PE prevention and its complications, as well as promising areas for further research. Keywords: preeclampsia, acetylsalicylic acid, pregnancy-associated plasma protein A, PAPP-A, placental growth factor, PlGF, placental abruption, first trimester screening, calcium. For citation: Osipov R.S., Dzhokhadze L.S., Kuznetsov P.A., Shamugiya V.V. Prevention of preeclampsia with acetylsalicylic acid: a brief history of use and modern prevention methods. Russian Journal of Woman and Child Health. 2023;6(4):368–373 (in Russ.). DOI: 10.32364/2618-8430-2023-6-4-7.